UiTM Mukah Bulletin: Inou Dengah UiTM Mukah? 4th Issue Volume 2 November 2025 - Mohd Samsi, Mohd Shafik; Kamaruddin, Siti Faridah; Joseph, Stefanie Natasha Rich; Robert, Cindy; Jafri, Fakhira; Jeri, Shirley Clare; Juhari, Nur Nadia Qausar (Corporate Communication Unit, UiTM Mukah Campus, 2025)
UiTM Mukah Bulletin: Inou Dengah UiTM Mukah? plays a vital role in highlighting the various activities taking place at UiTM Mukah Campus, whether involving students or staff members. Through social media platforms, this bulletin serves not only as a medium for sharing current information but also as a platform for recognizing the efforts and achievements of the campus community. From an academic perspective, research and scholarly initiatives by lecturers are also highlighted, acknowledging their valuable contributions to the advancement of knowledge and society. In addition, the publication of this bulletin helps foster a spirit of collaboration and unity among staff through their active participation in various activities and meaningful contribution of ideas.